Endoscopic Transoral Excision of Odontoid Process in Irreducible Atlantoaxial Dislocation: Our Experience of 34 Patients - Yadav, Yad Ram; Madhariya, Satya Narayan; Parihar, Vijay Singh; Namdev, Hehant; Bhatele, Pushp Raj (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background The endoscopic excision of the odontoid process in irreducible atlantoaxial dislocation (AAD) can be achieved by transnasal, transoral, and transcervical approaches. Endoscopic transoral technique has been found to be effective and safe. It avoids palatal splitting or prolonged retraction. We are reporting our experience of 34 cases. The relevant literature is reviewed.Material and Methods This was a prospective study of 34 patients treated during the past 5 years. Detailed history was taken and a thorough physical examination was made to record preoperative status. X-ray cervical spine lateral view (in neutral, flexion, and extension), anteroposterior (AP), and transoral view for the odontoid process were taken. Preoperative computed tomography (CT) and magnetic resonance imaging (MRI) scans and postoperative CT scans were done in all cases. Postoperative status at 1, 6, and 12 months was recorded.Results Age ranged from 15 to 56 years. There were 22 male and 12 female patients. Symptom duration ranged from 6 to 18 months.Preoperatively, there were 26 and 8 patients in Ranawat grades 3A and 3B, respectively. Five patients had tenth cranial nerve paresis. There were 23, 10, and 1 cases of AAD, AAD with basilar invasion, and tuberculosis, respectively. Palatal splitting was not required in any of the cases. All patients improved after surgery. No deaths occurred. One patient had cerebrospinal fluid (CSF) leak, which stopped after external lumbar drainage. Follow-up ranged from 12 to 65 months.Conclusion Endoscopic transoral odontoidectomy is a safe and effective alternative technique for odontoid excision. It can be performed in patients with small oral openings. Angled scopes improved exposure of clivus and palatal splitting was not required even in basilar invasion.
Keywords: atlantoaxial joint; dislocations; atlantoaxial fusion; endoscopic surgical procedures